Analysis of land carrying capacity of livestock and poultry breeding in China from the perspective of combination of planting and raising. Issue 1 (October 2020) - Zhu, Ning; Cao, Bo; Qin, Fu
Abstract: The separation and imbalance of planting and raising are the key issues to be solved urgently in China's agricultural development. In order to solve these problems, based on livestock manure nutrient supply and crop nutrient demand, this study uses the method released by the National Animal Husbandry Station to calculate and analyze the land carrying capacity of livestock and poultry breeding in China. The results indicate that, the supply of manure nitrogen from livestock and poultry was greater than that of phosphorus in 2017, there were large differences in the supply of livestock manure nitrogen and phosphorus from different livestock and poultry types and provinces, which was caused by the number of livestock and poultry in slaughtering, stock, breeding cycle, nutrient content of manure and the type in various provinces. The input of nitrogen and phosphorus in crops had exceeded the demand, which verified that it is feasible to reverse the problems of excessive fertilization and low utilization rate by reducing the amount of fertilization and replacing livestock manure with livestock manure. The index of land carrying capacity of livestock and poultry breeding in China was 0.48 and the number of livestock and poultry that could be carried was 5.921 billion pig equivalents, indicating that China's land could absorb livestock and poultry manure. In order to promote the combination of breeding and farming and the green development of agriculture, it was proposed to carry out the action of replacing fertilizer with manure for livestock and poultry according to local conditions, formulate a reasonable breeding policy based on the carrying capacity of livestock and poultry and propose countermeasures for coordinated development of planting and breeding.